Concurrent validity of the assessment tool for a health promotion program in Primary Health Care via telephone: a multilevel analysis - Marina Christofoletti; Paula Fabricio Sandreski; Humberto Moreira Carvalho; Cassiano Schuaste de Souza; Caroline Schramm Alves; Juciléia Barbosa Bezerra; Tania Rosane Bertoldo Benedetti (Revista Brasileira de Atividade Física e Saúde)
This study aims to verify the concurrent validity of the paper, and the telephone versions of the instrument used to evaluate the effectiveness of the Vida Ativa Melhorando a Saúde (VAMOS) Program participants. The VAMOS Program is a community-based intervention aiming at motivating people to adopt an active and healthy lifestyle. The sample for the validity test was two groups from different cities in Santa Catarina state. To compare each variable provided by paper and telephone format, multilevel generalized linear and logistic models were carried out, adjusted by age, sex, and school level. As a result, it was possible to identify the validity of most of the questions, with variations in the frequency of cooked vegetable consumption, method of preparing animal meat, frequency of physical activity, and waist circumference. We concluded that the use of the telephone survey could be considered for VAMOS Program evaluation.